دراﺳﺔ ﺗﺄﺛﯾر ﺑﻛﺗرﯾﺎ ﺣﺎﻣض اﻟﻼﻛﺗﯾك اﻟﻌﻼﺟﯾﺔ ﻓﻲ ﻧﻣو ﺑﻌض اﻧواع اﻟﺑﻛﺗرﯾﺎ اﻟﻣرﺿﯾﺔ ﺑﺣث ﻣﺳﺗل ﻣن رﺳﺎﻟﺔ ﻣﺎﺟﺳﺗﯾر (Journal of the College of Education for Women, 2019)
This investigation was carrid out to utilize whey and rice in manufacturing nutritious product with therapeutic virtue . The rice cooked with whey in a ratio 1:10 w/w, then the product was fermented by lactic acid bacteria (LAB) starters that comprise each Lb.acidophilus (Lb.a),Lb.casie(Lb.c) and their mixes at ratios: 1a:1c ;2a:1c ; 1a;2c . The five different starters were used separately in processing fermented products . The best fermentation period was 2 days as hieghest therapeutic bacterial counts were resulted . Antibacterial activity of LAB filtrate from fermented products were obtained before drying and after drying them after 3 months of storage. The tested bacteria were Staph.aureus, E.coli ,and B.subtilis The results reveald that filterated of LAB from processed product treatments have inhibitory effects on tested bacteria .Staph. aureus was the most liable ,the inhibiting zone were between10.03-19.0 mm., while the inhibitory zone of E.coli were between 10.1612.83 mm. The activity of LAB filtarate obtained from products after drying dropped as compared with the same products before drying.There were significant defferences (p≤0.05) among diameters of inhibition zones of tested bacteria for different products treatments. The largest inhibition zone diameters were for Lb.a products which valued 12.36 ,16.50 ,and 15.16 mm. forE.coli,Staph. aureus, and B.subtilis ,respectively. The inhibition effects of products filteratesdecreased gradually during storage period, so that the inhibition zone diameters became smaller for Lb.a. treatments at order of 48.86 ,40.6,and 43.07 % forE.coli,,Staph. aureus, and B.subtilis ,respectively. It had been observed that the inhibitory activity of Lb.a.filterrate with grater on the examined bacteria as compared with other filterate treatments during storage period.